2000
DOI: 10.1101/lm.7.3.140
|View full text |Cite
|
Sign up to set email alerts
|

Operant Conditioning in Lymnaea: Evidence for Intermediate- and Long-term Memory

Abstract: Aerial respiration of the pond snail, Lymnaea stagnalis, can be operantly conditioned; however, the parameters necessary to produce long-term (LTM) or intermediate term memory (ITM) have not previously been investigated. We conducted training using procedures that varied in the duration of the training session, the number of training sessions per day or the amount of time between subsequent training sessions (SI). We found that by varying the duration and frequency of the training session learning could be dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 28 publications
3
129
0
Order By: Relevance
“…Changes in protein synthesis that occur locally and extrasomally (Martin et al 1997;Spencer et al 2000) are hypothesized to underlie this form of memory. Whether a change in context will also affect the ability to retrieve ITM is now being studied using a procedure that only produces ITM (Lukowiak et al 2000a). These experiments and results described here extend the usefulness of operant conditioning of aerial respiration in Lymnaea as a model system in which to directly study how learning and the different forms of memory are mediated at the neuronal level.…”
Section: Haney and Lukowiakmentioning
confidence: 82%
See 3 more Smart Citations
“…Changes in protein synthesis that occur locally and extrasomally (Martin et al 1997;Spencer et al 2000) are hypothesized to underlie this form of memory. Whether a change in context will also affect the ability to retrieve ITM is now being studied using a procedure that only produces ITM (Lukowiak et al 2000a). These experiments and results described here extend the usefulness of operant conditioning of aerial respiration in Lymnaea as a model system in which to directly study how learning and the different forms of memory are mediated at the neuronal level.…”
Section: Haney and Lukowiakmentioning
confidence: 82%
“…Thus, transcriptional blockers applied just after training prevent the formation of LTM but not intermediate-term memory (ITM). ITM, which persists for only 2-3 h in Lymnaea (Lukowiak et al 2000a), is also dependent on new protein synthesis but not altered gene activity. Thus, using a translational blocker, Scheibenstock and Lukowiak (2000) showed that ITM could be blocked.…”
Section: Haney and Lukowiakmentioning
confidence: 99%
See 2 more Smart Citations
“…Aversive operant conditioning of Lymnaea's aerial respiratory behavior involves stimulating the animal's pneumostome when it surfaces and attempts to breathe (Lukowiak et al, 1996(Lukowiak et al, , 1998(Lukowiak et al, , 2000Lukowiak and Syed, 1999;Spencer et al, 1999;Haney and Lukowiak, 2001;McComb et al, 2002McComb et al, , 2003Sangha et al, 2002Sangha et al, , 2003Scheibenstock et al, 2002;Spencer et al, 2002). The stimulation is aversive, which leads to the animal closing the pneumostome and learning as training progresses to reduce its attempts to open the pneumostome.…”
Section: Invertebrate Operant Conditioningmentioning
confidence: 99%